2022
DOI: 10.1186/s42234-022-00099-7
|View full text |Cite
|
Sign up to set email alerts
|

Electric field responsive nanotransducers for glioblastoma

Abstract: Background Electric field therapies such as Tumor Treating Fields (TTFields) have emerged as a bioelectronic treatment for isocitrate dehydrogenase wild-type and IDH mutant grade 4 astrocytoma Glioblastoma (GBM). TTFields rely on alternating current (AC) electric fields (EF) leading to the disruption of dipole alignment and induced dielectrophoresis (DEP) during cytokinesis. Although TTFields have a favourable side effect profile, particularly compared to cytotoxic chemotherapy, survival benefi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Another possible mechanism that could be considered is the behavior of GNPs as electric field transducers. 29 In this case, the polarization of GNPs in presence of AC could allow them to interact with plasma membrane in a way that facilitates their movements outwards. However, it is unclear how HF-AC could manipulate endosomal membrane, thus highlighting the need for new investigations on understanding the underlying mechanism such as AC mediated proton sponge effect.…”
Section: Endo/lysosomal Escape Of Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible mechanism that could be considered is the behavior of GNPs as electric field transducers. 29 In this case, the polarization of GNPs in presence of AC could allow them to interact with plasma membrane in a way that facilitates their movements outwards. However, it is unclear how HF-AC could manipulate endosomal membrane, thus highlighting the need for new investigations on understanding the underlying mechanism such as AC mediated proton sponge effect.…”
Section: Endo/lysosomal Escape Of Gold Nanoparticlesmentioning
confidence: 99%
“…18 Our group has recently shown that AC could bypass the plasma membrane to exert effects across the cell membrane. 16, 19 Moreover, it has been established that electrical input on lipid bilayers causes subtle structural perturbations in their structure. 20 Therefore, we hypothesized that by exploiting electrical input intracellular fate of nanoparticle-based delivery systems for anti-cancer therapy could be modulated.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the observed decrease of metabolic activity of GNP100@rC@Z treated cells was significantly higher than that following 24-hour application of FDA approved Tumour treating Fields (TTFs) in vitro . 28,29 We ascribe this significant decrease in metabolic activity to the electrical-molecular communication via redox switching of rC to oxidised form of C (oC), thus inducing cell stress. To eliminate any potential effect of applied 1 V on water electrolysis (1.23 V vs normal hydrogen electrode), we chose 0.65 V/cm for further studies.…”
Section: Figurementioning
confidence: 99%
“…cancer) cells (Kirson et al 2007). The role of the intracellular anti-cancer properties of certain electrical fields, summarized as therapeutic alternating electrical fields or AEF are mediated by bipolar dielectrophoretic and electrophoretic effects (Kirson et al 2004, Jain et al 2022. Since the identification of this initial mechanism of action, multiple other mechanisms have been identified, ranging from permeabilization of cancer cell membranes (Chang et al 2018) to altered cancer cell metabolism (Patel et al 2021) and a modulation of immune response (Chen et al 2022, Lee et al 2022.…”
Section: Introductionmentioning
confidence: 99%